The value of cytokeratin immunohistochemistry in the evaluation of axillary sentinel lymph nodes in patients with lobular breast carcinoma. Issue 5 (23rd February 2006) - Cserni, G; Bianchi, S; Vezzosi, V; Peterse, H; Sapino, A; Arisio, R; Reiner-Concin, A; Regitnig, P; Bellocq, J-P; Marin, C; Bori, R; Penuela, J M; et al.
Abstract : Background: Cytokeratin immunohistochemistry (IHC) reveals a higher rate of occult lymph node metastases among lobular carcinomas than among ductal breast cancers. IHC is widely used but is seldom recommended for the evaluation of sentinel lymph nodes in breast cancer patients. Objective: To assess the value of cytokeratin IHC for the detection of metastases in sentinel lymph nodes of patients with invasive lobular carcinoma. Methods: The value of IHC, the types of metastasis found by this method, and the involvement of non-sentinel lymph nodes were analysed in a multi-institutional cohort of 449 patients with lobular breast carcinoma, staged by sentinel lymph node biopsy and routine assessment of the sentinel lymph nodes by IHC when multilevel haematoxylin and eosin staining revealed no metastasis. Results: 189 patients (42%) had some type of sentinel node involvement, the frequency of this increasing with increasing tumour size. IHC was needed for identification of 65 of these cases: 17 of 19 isolated tumour cells, 40 of 64 micrometastases, and 8 of 106 larger metastases were detected by this means. Non-sentinel-node involvement was noted in 66 of 161 cases undergoing axillary dissection. Although isolated tumour cells were not associated with further lymph node involvement, sentinel node positivity detected by IHC was associated with further nodal metastases in 12 of 50 cases (0.24), a proportion that is higher than previously reported for breast cancer in general. Conclusions: IHC is recommended for the evaluation of sentinel nodes from patients with lobular breast carcinoma, as the micrometastases or larger metastases demonstrated by this method are often associated with a further metastatic nodal load.